Orwell's Homage to Catalonia in Catalan and Spanish translation. - Marco, Josep (Perspectives: Studies in Translatology, 2021)
This article examines the Catalan and Spanish translations of George Orwell's Homage to Catalonia published by Ariel in 1969 and 1970 (respectively) from two perspectives: that of the censorship files preserved at the Archivo General de la Administración in Alcalá de Henares, and that of the published translations. First, relevant information is provided on the setting in which those translations were published, as regards institutionalised censorship and the reception of Orwell's work under Franco. This is followed by analysis of data from the files and from the texts. Such an analysis allows us to determine in the present case that, whereas the censor's injunctions were mostly followed by the publisher, advantage was also taken of the censor's hesitations to preserve as much of the source text's memorial content as possible in the translations. Results of the analysis are finally linked with general concepts at the interface of translation and memory studies. If translators and publishers are seen as secondary witnesses in accounts of traumatic events, then censors may be regarded as tertiary witnesses, and censored texts as sites of dialectic tension between memory and forgetting.